Feed additives for swine: Fact sheets – acidifiers and antibiotics - Jacela, Jay Y.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Renter, David G.; Dritz, Steven S. (My University, 2012)
Feed additives are non-nutritive products used in swine diets to improve production efficiency and performance. If chosen carefully and used properly, feed additives can be effective and can help increase the profitability of pig production. Not all feed additives are the same or provide a beneficial response and, therefore, choosing a product will depend on the farm’s specific situation and needs. This series of fact sheets includes some of the major classifications of products used as feed additives. Every effort has been made to ensure that all the information in every fact sheet is current and based on the latest scientific publications available at the time of writing. The objective of these fact sheets is to discuss some of the basic concepts to help producers improve their understanding of these products. They also aim to promote more responsible and judicious use of feed additives. Beneficial claims from dietary inclusions of acidifiers include control of bacterial growth in feed, increased growth performance, improvement in nutrient digestibility, and control of harmful bacteria in the gut. Antimicrobial agents, such as antibiotics, have been used in pig production for over 50 years. Early studies indicated significant improvements in pig growth performance when antibiotics were fed. With the improvements in production practices and health status of pig herds, positive responses to in-feed antibiotics may not be as large in today’s modern facilities. Additionally, the magnitude of response differs with the stage of pig growth. Use of antibiotics as feed additives is subject to regulatory policies to prevent residues and enhance public health. It is therefore important to be aware of the current information available concerning the effects of commonly used in-feed antibiotics in pig production.
Keywords: Swine; Acidifiers; Antibiotics; Performance; Production efficiency